Burning Fire-Prone Mediterranean Shrublands: Immediate Changes in Soil Microbial Community Structure and Ecosystem Functions - Goberna, M.; García, C.; Insam, H.; Hernández, M. T.; Verdú, M. (Microbial ecology, 2012)
Wildfires subject soil microbes to extreme temperatures and modify their physical and chemical habitat. This might immediately alter their community structure and ecosystem functions. We burned a fire-prone shrubland under controlled conditions to investigate (1) the fire-induced changes in the community structure of soil archaea, bacteria and fungi by analysing 16S or 18S rRNA gene amplicons separated through denaturing gradient gel electrophoresis; (2) the physical and chemical variables determining the immediate shifts in the microbial community structure; and (3) the microbial drivers of the change in ecosystem functions related to biogeochemical cycling. Prokaryotes and eukaryotes were structured by the local environment in pre-fire soils. Fire caused a significant shift in the microbial community structure, biomass C, respiration and soil hydrolases. One-day changes in bacterial and fungal community structure correlated to the rise in total organic and NO₃⁻-N caused by the combustion of plant residues. In the following week, bacterial communities shifted further forced by desiccation and increasing concentrations of macronutrients. Shifts in archaeal community structure were unrelated to any of the 18 environmental variables measured. Fire-induced changes in the community structure of bacteria, rather than archaea or fungi, were correlated to the enhanced microbial biomass, CO₂ production and hydrolysis of C and P organics. This is the first report on the combined effects of fire on the three biological domains in soils. We concluded that immediately after fire the biogeochemical cycling in Mediterranean shrublands becomes less conservative through the increased microbial biomass, activity and changes in the bacterial community structure.